1994
DOI: 10.1143/jjap.33.6913
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Mask Inspection Using Replicated Resist Patterns

Abstract: A new X-ray mask inspection method using replicated resist patterns is proposed. It is able to detect fatal opaque defects on the back surface of the mask and at the bottom of the hole pattern, in addition to those on the front surface. It can also ignore transparent defects on the mask. This method is useful even for defect detection on a single-die mask through die-to-die comparison. For the false process defects occurring during the replication process, a discrimination procedure us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Figure 4 (c) shows the printed resist pattern (SAL-601), which is used for the mask inspection. 6 We confirmed that the opaque defects of the Ta absorber were completely repaired.…”
Section: Opaque Defect Repairsupporting
confidence: 69%
“…Figure 4 (c) shows the printed resist pattern (SAL-601), which is used for the mask inspection. 6 We confirmed that the opaque defects of the Ta absorber were completely repaired.…”
Section: Opaque Defect Repairsupporting
confidence: 69%
“…[31][32][33] To evaluate the printability of defects and repaired patterns, the mask defects were inspected by using replicated resist patterns. The defect density of x-ray masks was about 5/cm 2 .…”
Section: Device Characteristicsmentioning
confidence: 99%
“…The mask defects come from mask fabrication processes (3), contamination during the exposure (2), and adhesion of particles during mask-handling (4). The CD errors due to mask defects depend not only on above defect types but also on the exposure conditions.…”
Section: Introductionmentioning
confidence: 99%